2016
DOI: 10.1165/rcmb.2015-0306oc
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Antiviral Stress Granule and IFN-β Enhanceosome Formation Enhances Susceptibility to Influenza Infection in Chronic Obstructive Pulmonary Disease Epithelium

Abstract: Chronic obstructive pulmonary disease (COPD) is a serious lung disease that progressively worsens lung function. Those affected are highly susceptible to influenza virus infections that result in exacerbations with exaggerated symptoms with increased mortality. The mechanisms underpinning this increased susceptibility to infection in COPD are unclear. In this study, we show that primary bronchial epithelial cells (pBECs) from subjects with COPD have impaired induction of type I IFN (IFN-β) and lead to heighten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 38 publications
3
43
0
Order By: Relevance
“…We have previously shown that human influenza H3N2 infection induced heightened inflammatory responses (25), and high pathogenic avian H5N1is known to induce severe cytokine storms in the lung (9,26). We also showed that primary BECs (pBECs) from COPD subjects and our established in vivo model of experimental COPD have increased inflammatory and impaired antiviral responses to IAV infections, leading to more severe infection (27)(28)(29). Furthermore, miRNAs are known to be altered in COPD (30,31).…”
Section: Introductionmentioning
confidence: 70%
“…We have previously shown that human influenza H3N2 infection induced heightened inflammatory responses (25), and high pathogenic avian H5N1is known to induce severe cytokine storms in the lung (9,26). We also showed that primary BECs (pBECs) from COPD subjects and our established in vivo model of experimental COPD have increased inflammatory and impaired antiviral responses to IAV infections, leading to more severe infection (27)(28)(29). Furthermore, miRNAs are known to be altered in COPD (30,31).…”
Section: Introductionmentioning
confidence: 70%
“…The clinical course of COPD is complicated by frequent episodes of acute exacerbations, which primarily involves microbial and viral infections 91 , 126 , 127 . In the past two decades, our understanding of the pathogenesis of airway infections has increased substantially.…”
Section: The Role Of the Microbiome In Copdmentioning
confidence: 99%
“…12 An abnormal innate immune response to VRIs has been reported to increase the susceptibility to viral infection in patients with chronic obstructive pulmonary disease (COPD), asthma, or cystic fibrosis, triggering disease exacerbation. [14][15][16][17][18] Airway epithelial cells from asthmatic patients produced less IFN-b and IFN-l and showed deficient innate immunity for rhinovirus infection. 14,16 IFN-b levels were also reduced in epithelial cells obtained from children with wheezing and atopy after respiratory syncytial virus infection.…”
mentioning
confidence: 99%